Staff councils in hospitals as co-managers? A blind spot in codetermination research; Agieren Personalraẗe in Krankenhaüsern als Co-Manager? Ein blinder Fleck in der Mitbestimmungsforschung - Stefan Bar̈; Sebastian Starystach; Heike Hess (Industrielle Beziehungen, 2021)
New Public Management (NPM) has triggered far-reaching transformations within hospital sectors worldwide and professionalized hospital management has put employee representation under pressure. In this context the current state of research points out that codetermination actors are taking increasingly over the role of co-managers. To test this hypothesis, the cognitive and normative structures in the mind-sets of staff council members at four German university hospitals have been reconstructed on the bases of problem-centered interviews. The results show that the structural change in the German hospital sector affects employee representation in university clinics extensively. However, there is no clear-cut development towards a co-management orientation within the mind-sets of the staff council members. On the contrary, co-management is rejected in varying degrees. The reason for that being is that staff councils in German university hospitals, in addition to their institutional codetermination function, see themselves closely linked to the institutional mission of providing a public good. This is firmly embedded in the cognitive and normative structures of the mindsets. Although the study focusses on a very specific area of co-determination, it exemplifies how the political agenda of the NPM can irritate and break institutionalized patterns in industrial relations. – – Das New Public Management (NPM) hat weltweit weitreichende Transformationen innerhalb des Krankenhaussektors ausgelos̈t und mit einem zunehmend professionalisierten Krankenhausmanagement ist seither die Beschaf̈tigtenvertretung neuen Herausforderungen ausgesetzt. Im gegenwar̈tigen Forschungsstand wird darauf verwiesen, dass sich Mitbestimmungsakteure in diesem Zusammenhang zu Co-Managern entwickeln. Um diese These zu pruf̈en, wurden problemzentrierte Interviews mit Personalratsmitgliedern an vier deutschen Universitaẗskliniken gefuḧrt und mit Hilfe der Collective-Mindset-Analyse auf kognitive und normative Strukturen hin ausgewertet. Es zeigt sich, dass der Strukturwandel im Krankenhaussektor umfangreiche Auswirkungen auf die Arbeitnehmervertretung hat. Eine klare Co-Management-Orientierung zeigt sich jedoch nicht. Im Gegenteil, sie wird in unterschiedlichem Maße abgelehnt. Das las̈st sich dadurch erklar̈en, dass sich Personalratsmitglieder in deutschen Universitaẗskliniken neben ihrer institutionellen Mitbestimmungsfunktion eng mit dem institutionellen Auftrag der Daseinsvorsorge verbunden sehen. Dies ist kognitiv und normativ fest in denMindsets verankert. Auch wenn sich die Studie lediglich auf einen kleinen Bereich der Mitbestimmung konzentriert, verweisen die Ergebnisse darauf, dass die politische Agenda des NPM institutionalisierte Muster in den industriellen Beziehungen irritieren und aufbrechen kann.
Keywords: J53; L39; 330; Public hospitals; commodification; staff councils; co-management; New Public Management; Of̈fentliche Krankenhaüser; Ok̈onomisierung; Personalraẗe; Co-Management; New Public Management.